Reframing the covenant: A Solemn Acknowledgment (1648) and the resubscription of the Solemn League and Covenant. Issue 5 (3rd September 2022) - McIntyre, Neil; McDougall, Jamie
ABSTRACT: The Solemn League and Covenant, having first been subscribed in 1643, was commanded to be subscribed again in 1648 by the Commission of the General Assembly of the Church of Scotland and the Committee of Estates of the Scottish Parliament. As part of this nationwide resubscription process, which was managed by the lower church courts, ministers read aloud an explanatory document, A Solemn Acknowledgment of Publick Sins and breaches of the Covenant, before their congregations. By assessing the design, delivery and reception of the resubscription campaign, this article seeks to shed light on this significant but largely overlooked moment in the seventeenth-century British revolutions. It reflects also on the intellectual and cultural legacies of this episode, revealing in particular its role in the development of Presbyterian dissent in Scotland as well as its seeding of an idea of governmental accountability in Scottish political thought.